Performance Enhancement of Electronic Chipset by the Successive Cooling System - Salman, Ali (Anbar Journal of Engineering Sciences, 2025)
The performance of electronic devices, especially computers, depends on the efficiency of the electronic chips and Computer processing units, which are mainly made of semiconductors, so their working efficiency is inversely proportional to their working temperature. Therefore, this paper presents an experimental investigation of the design, implementation, and testing of three cooling systems to maintain the temperature of the processing unit as minimum as possible. The first is a traditional system dissipates heat from the working fluid to the air through a finned tube heat exchanger. The second successive hybrid system was designed to integrate with the first one in addition to a thermoelectric cooling system to cool the working fluid. The third system included in addition to the traditional heat dissipation one, an intercooler cylinder with a large quantity of the working fluid in the main system beside a separate system for cooling the working fluid using thermoelectric cooling to ensure sufficient cooling of the processing units when working at high frequencies by providing a large capacity of working fluid pre-cooled to a low temperature. Comparing the experimental results of the cooling systems with the traditional one under the same test conditions showed that the second system led to a reduction in the temperature of the processing unit by 5.2%, while employing the third system reduced the temperature to 11.3%., When the thermoelectric cooling unit operates at a performance factor of about 1.76.